Richard M. Nixon correspondence - Nixon, Richard M. (Richard Milhous), 1913-1994.
Photocopy of the resignation letter (1974 August 9) from Nixon to U.S. Secretary of State Henry Kissinger.
U.S. president and vice-president, U.S. senator and representative from California, and lawyer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kissinger, Henry, -- 1923- -- Correspondence; Watergate Affair, 1972-1974.; United States -- Politics and government -- 1969-1974.; Lawyers; Presidents -- United States; Representatives, U.S. Congress -- California; Senators, U.S. Congress -- California; Vice-Presidents -- United States